2018
DOI: 10.1507/endocrj.ej17-0491
|View full text |Cite
|
Sign up to set email alerts
|

Improved cardiometabolic risk factors in Japanese patients with type 2 diabetes treated with ipragliflozin: a pooled analysis of six randomized, placebo-controlled trials

Abstract: To examine differential improvements among cardiovascular risk factors in response to treatment with ipragliflozin in Japanese type 2 diabetes mellitus (T2DM) patients, we conducted a pooled analysis of six randomized, double-blind trials of Japanese T2DM patients who received ipragliflozin 50 mg/day or placebo and had patient-level data for cardiometabolic risk parameters. Risk factors included glycated hemoglobin (HbA1c), body weight, homeostatic model assessment for insulin resistance and beta-cell function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 47 publications
(61 reference statements)
0
16
1
1
Order By: Relevance
“…In a preliminary randomized, parallelgroup study of Japanese patients with T2DM, patients treated with ipragliflozin experienced a statistically significant reduction from baseline in small dense LDL-C levels and an increase in LDL particle size [52]. In contrast, in a pooled analysis of six randomized, double-blind trials of ipragliflozin, no improvement in LDL-C or non HDL-C levels was found despite improvements in other cardiometabolic risk factors [53]. The results of the present study provide further, real-world, support for improvements in lipid parameters with long-term ipragliflozin therapy.…”
Section: Discussionmentioning
confidence: 94%
“…In a preliminary randomized, parallelgroup study of Japanese patients with T2DM, patients treated with ipragliflozin experienced a statistically significant reduction from baseline in small dense LDL-C levels and an increase in LDL particle size [52]. In contrast, in a pooled analysis of six randomized, double-blind trials of ipragliflozin, no improvement in LDL-C or non HDL-C levels was found despite improvements in other cardiometabolic risk factors [53]. The results of the present study provide further, real-world, support for improvements in lipid parameters with long-term ipragliflozin therapy.…”
Section: Discussionmentioning
confidence: 94%
“…In addition to improved glycaemic control [516], SGLT2 inhibitors provide important clinical benefits for patients with T2DM. Unlike most other anti-hyperglycaemic agents, SGLT2 inhibitors promote weight loss [15, 17], lower blood pressure [1821] and exert beneficial effects on other cardiometabolic risk factors, except for low-density lipoprotein cholesterol and non-high-density lipoprotein cholesterol [22]. Indeed, patients with T2DM at high risk for cardiovascular (CV) events have been shown to have a lower incidence of CV outcomes and death after treatment with SGLT2 inhibitors [2327].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the EMPA-REG OUTCOME trial (8,9) and the CANVAS program (14,15) reported that the beneficial effects of SGLT2 inhibitors on the eGFR occurred concomitantly with glycemic improvements. The reduction in the UA levels was also observed concurrently with the improvement in the glucose metabolism following SGLT2 inhibitor administration (28)(29)(30)(31)(32). These results suggest that the renal benefits of SGLT2 inhibitors are involved in the changes in several parameters, including UA levels and glucose metabolism.…”
Section: Discussionmentioning
confidence: 57%